Professor Shlomo Simonsohn ז״ל - Zeldes, Nadia (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2019)
Profilo bio-bibliografico di Shlomo Simonsohn (1923-2019) nel ricordo di Nadia Zeldes. * A bio-bibliographical sketch of Shlomo Simonsohn (1923-2019) as remembered by Nadia Zeldes.